Phylogeny, adaptive evolution, and taxonomy of Acronema (Apiaceae): evidence from plastid phylogenomics and morphological data - Chen, Lian; Song, Bo-Ni; Yang, Lei; Wang, Yuan; Wang, Yun-Yi; Aou, Xueyimu; He, Xing-Jin; Zhou, Song-Dong (Frontiers in Plant Science, 2024)
The genus Acronema, belonging to Apiaceae, includes approximately 25 species distributed in the high-altitude Sino-Himalayan region from E Nepal to SW China. This genus is a taxonomically complex genus with often indistinct species boundaries and problematic generic delimitation with Sinocarum and other close genera, largely due to the varied morphological characteristics. To explore the phylogenetic relationships and clarify the limits of the genus Acronema and its related genera, we reconstructed a reliable phylogenetic framework with high support and resolution based on two molecular datasets (plastome data and ITS sequences) and performed morphological analyses. Both phylogenetic analyses robustly supported that Acronema was a non-monophyletic group that fell into two clades: Acronema Clade and East-Asia Clade. We also newly sequenced and assembled sixteen Acronema complete plastomes and performed comprehensively comparative analyses for this genus. The comparative results showed that the plastome structure, gene number, GC content, codon bias patterns were high similarity, but varied in borders of SC/IR. The SC/IR boundaries of Acronema chienii were significantly different from the other Acronema members. We also identified twelve potential DNA barcode regions (ccsA, matK, ndhF, ndhG, psaI, psbI, rpl32, rps15, ycf1, ycf3, psaI-ycf4 and psbM-trnD) for species identification in Acronema. The molecular evolution of Acronema was relatively conservative that only one gene (petG) was found to be under positive selection (ω = 1.02489). The gene petG is one of the genes involved in the transmission of photosynthetic electron chains during photosynthesis, which plays a crucial role in the process of photosynthesis in plants. This is also a manifestation of the adaptive evolution of plants in high-altitude areas to the environment. In conclusion, our study provides novel insights into the plastome adaptive evolution, phylogeny, and taxonomy of genus Acronema.